Communicable Diseases Surveillance: CDI volume 22 issue 12 (1998) - No authors listed (Communicable Diseases Intelligence, 1998)
Communicable diseases surveillance outcomes from several reporting series as follows: Communicable Diseases Surveillance: Highlights (vaccine preventable diseases, arboviruses, respiratory viruses); National Notifiable Diseases Surveillance System tables, 14 October to 10 November 1998; Laboratory Serology and Virology Reporting Scheme tables, 8 October to 4 November 1998; Australian Sentinel Practice Research Network report tables, weeks 40 to 43, 1999; Gonococcal surveillance, reporting period 1 April to 30 June 1998; Sentinel chicken surveillance program, reporting period September 1998; HIV and AIDS surveillance, reporting period 1 to 30 June 1998, assessed as at 30 September 1998; Australian childhood immunisation coverage, 1 April to 30 June 1998 cohort, assessed as at 30 June 1998.